Clinical Pharmacokinetics and Pharmacodynamics of Cerliponase Alfa, Enzyme Replacement Therapy for CLN2 Disease by Intracerebroventricular Administration. Issue 2 (30th November 2020) - Kim, Aryun; Grover, Anita; Hammon, Kevin; de Hart, Greg; Slasor, Peter; Cherukuri, Anu; Ajayi, Temitayo; Jacoby, David; Schulz, Angela; Specchio, Nicola; de Los Reyes, Emily; Gissen, Paul; et al.
Abstract : Cerliponase alfa is recombinant human tripeptidyl peptidase 1 (TPP1) delivered by i.c.v. infusion for CLN2, a pediatric neurodegenerative disease caused by deficiency in lysosomal enzyme TPP1. We report the pharmacokinetics (PK) and pharmacodynamics of cerliponase alfa, the first i.c.v. enzyme replacement therapy, characterized in a phase I/II study. Escalating doses (30–300 mg Q2W) followed by 300 mg Q2W for ≥ 48 weeks were administered in 24 patients aged ≥ 3 years. Concentrations peaked in cerebrospinal fluid (CSF) at the end of 4‐hour i.c.v. infusion and 8 hours thereafter in plasma. Plasma exposure was 300–1, 000‐fold lower than in CSF, with no correlation in the magnitude of peak concentration (Cmax ) or area under the concentration‐time curve (AUC) among body sites. There was no apparent accumulation in CSF or plasma exposure with Q2W dosing. Interpatient and intrapatient variability of AUC, respectively, were 31–49% and 24% in CSF vs. 59–103% and 80% in plasma. PK variability was not explained by baseline demographics, as sex, age, weight, and CLN2 disease severity score did not appear to impact CSF or plasma PK. No apparent correlation was noted between CSF or plasma PK and incidence of adverse events (pyrexia, hypersensitivity, seizure, and epilepsy) or presence of antidrug antibodies in CSF and serum. There was no relationship between magnitude of CSF exposure and efficacy (change in CLN2 score from baseline), indicating maximum benefit was obtained across the range of exposures with 300 mg Q2W. Data from this small trial of ultra‐rare disease were leveraged to adequately profile cerliponase alfa and support 300 mg i.c.v. Q2W for CLN2 treatment.